Relationships between self-efficacy and personal hardiness and pain self-efficacy in university students - Seyed Mousa Golestaneh (Gonabad University of Medical Sciences, 2018)
Self-efficacy beliefs are used to explain a range of behaviors and aspects of the pain experience. The aim of this study was to determine the relationship between academic self-efficacy, social self-efficacy, emotional self-efficacy and psychological hardiness with pain self-efficacy in students. 167 students of Persian Gulf university were selected randomly. The research tools consist of Nicholas pain self-efficacy questionnaire, Morris pain self-efficacy questionnaire and Kobasa psychological hardiness. Correlation coefficient results showed that there was a significant separate correlation between academic self-efficacy, social self-efficacy, emotional self-efficacy, and psychological hardiness with pain self-efficacy. The results of regression analysis showed that the best predictors of pain self-efficacy were psychological hardiness, emotional self-efficacy and social self-efficacy, respectively. Totally the results of regression analysis were significant and revealed that the multiple relationship of predictor variables with the criterion variable was approved. The results suggest that the psychological hardiness and emotional self-efficacy play very effective role in dealing with aches and pains for students.